Zakonite oblike opravljanja dela - Senčur Peček, Darja (Podjetje in delo, 2013)
The article deals with various forms of performing work in the Republic of Slovenia and their legal regulation, especially the new one. Beside this, the possible misuses and illegal practices are pointed out.
Keywords: delovne pogodbe; delovno pravo; pogodba o zaposlitvi